Rag1 immunodeficiency‐induced early aging and senescence in zebrafish are dependent on chronic inflammation and oxidative stress. Issue 5 (26th July 2019) - Novoa, Beatriz; Pereiro, Patricia; López‐Muñoz, Azucena; Varela, Mónica; Forn‐Cuní, Gabriel; Anchelin, Monique; Dios, Sonia; Romero, Alejandro; Martinez‐López, Alicia; Medina‐Gali, Regla María; Collado, Manuel; Coll, Julio; et al.
Abstract: In mammals, recombination activating gene 1 (RAG1) plays a crucial role in adaptive immunity, generating a vast range of immunoglobulins. Rag1 −/− zebrafish ( Danio rerio ) are viable and reach adulthood without obvious signs of infectious disease in standard nonsterile conditions, suggesting that innate immunity could be enhanced to compensate for the lack of adaptive immunity. By using microarray analysis, we confirmed that the expression of immunity‐ and apoptosis‐related genes was increased in the rag1 −/− fish. This tool also allows us to notice alterations of the DNA repair and cell cycle mechanisms in rag1 −/− zebrafish. Several senescence and aging markers were analyzed. In addition to the lower lifespan of rag1 −/− zebrafish compared to their wild‐type (wt) siblings, rag1 −/− showed a higher incidence of cell cycle arrest and apoptosis, a greater amount of phosphorylated histone H2AX, oxidative stress and decline of the antioxidant mechanisms, an upregulated expression and activity of senescence‐related genes and senescence‐associated β‐galactosidase, respectively, diminished telomere length, and abnormal self‐renewal and repair capacities in the retina and liver. Metabolomic analysis also demonstrated clear differences between wt and rag1 −/− fish, as was the deficiency of the antioxidant metabolitel ‐acetylcarnitine (ALCAR) in rag1 −/− fish. Therefore, Rag1 activity does not seem to be limited to V(D)J recombination but is also involved in senescence and aging. Furthermore, we confirmed the senolytic effect of ABT‐263, a known senolytic compound and, for the first time, the potential in vivo senolytic activity of the antioxidant agent ALCAR, suggesting that this metabolite is essential to avoid premature aging. Abstract : Rag1 immunodeficiency‐induced early aging and senescence in zebrafish are dependent on chronic inflammation and oxidative stress. One‐year‐old rag1 −/− mutants show higher β‐gal activity in the skin than wt fish.